Pola Komunikasi Orang Tua dengan Anak terhadap Ketergantungan Media Internet di BTN Gowa Lestari Batangkaluku - Andrianto Andrianto; Dwi Noviatul Zahra; Nurul Aisyah (SELING: Jurnal Program Studi PGRA, 2021)
The Internet is a global information network that can be accessed via a home computer, modem, smartphone, internet cafe, and through other services, namely Web-TV. However, there are some people who are against the internet as a new mass medium available the public. This research’s goals are twofold: (1) determining the pattern of communication between parents and adolescents when overcoming the internet media dependency in BTN Gowa Lestari Batangkalukuand (2) identifying possible strategies to break the communication barriers between parents and adolescents who experienced the dependency of internet media. This research is a descriptive qualitative using and approach based on Media System Dependency theory as developed by Krisnawati (2016). The data sources of this study included parents and adolescents in BTN Gowa Lestari Batangkaluku. The informants were 6 people: 3 parents(1 female and 2 males), and 3 teenagers. Furthermore, the techniques used for data collection consist of: observation, interviews, and documental research. Based on the discussions of the research results, it can be argued that (1) there are 2 types of communication patterns used by parents when it comes to internet dependence at BTN Gowa Lestari Batangkaluku, them being: (a) permissive communication patterns that leave the children free to do anything, and (b) authoritative communication patterns where parents and children discuss all the rules in the house. The results of this study indicate that, (2) when communicating with teenagers parents experience a series of obstacles. Said barriers of communication between parents and adolescents being, for example: lack of time to spend with the children, business and work, lack of knowledge concerning the internet, irritability due to fatigue after work, parents not focusing on taking care of and supervising their children, and selfishness from both children and parents. Research implications, as well as suggestions are: (1) for parents to improve the quality of the approach by making it less incisive, improving their communication skills, understanding their role as a parent and providing appropriate solutions to their children so that they are not overly dependent on the internet; 2) for them to take extra time for the children and supervise them when using the internet, so that in the future parents have a strategy in deeper understanding when dealing with problems relating to internet consumption. Finally, (3) for teenagers, it is suggested to try to fill their free time with positive things and strengthen their relationship with their parents, by being willing to tell what problems they are facing more openly, so that their connection with their parents is stronger.